Penggunaan Qr Code Sarana Penyampaian Promosi Dan Informasi Kebun Binatang Berbasis Android - Adiguna Wijaya - STMIK Nusa Mandiri Jakarta; A. Gunawan - AMIK BSI Sukabumi (Bianglala Informatika, 2016)
Abstract - Use Of QR Code Submission Facility Promotions And Informations On Zoo Based Android. The QR (Quick Response) code is a two-dimensional barcode developed by the Japanese company Denso-Wave in 1994, and was approved as an ISO International Standard and Chinese National Standard in 2000. Biodiversity, the most fascinating aspect of biology, includes variability among living organisms from all sources including interalia, terrestrial, marine and other aquatic ecosystems and the ecological complexes of which they are part it includes diversity within species and ecosystem. The purpose of writing this paper is to understand the types of biodiversity and to conserve biodiversity to visitors. The method used in writing this paper with reference to study literature and journals, authors are looking for materials via the internet. Management of the zoo require visitors for the survival and progress of the management of the zoo, for the promotion and dissemination of information becomes important. In this digital age of information can be easily accessed by facilities which the number of smartphone users continues to grow each year, and could be a captive market for the zoo. The zoo has not utilize media technology to the needs management of information facilities and promotion. Use of QR code application makes it easy for visitors to the zoo because of access to information and the promotion of far more effective and flexible for visitors, because it no longer need to access several times to get information and promotions. With the application of QR code management of zoo can harness and use as a medium of information and media promotions for visitors the zoo. QR code application that for used submission facilities promotion and information at the zoo is ZXing Library. Key Word : QR code, Promotions, Informations, Zoo, Smartphone Android   Abstrak - QR (Quick Response) kode adalah dua dimensi barcode yang dikembangkan oleh perusahaan Jepang Denso-Wave di tahun 1994, dan telah disetujui sebagai standar internasional ISO dan Standar Nasional Cina pada tahun 2000. Keanekaragaman hayati, aspek yang paling menarik dari biologi, termasuk variabilitas antara organisme hidup dari semua sumber termasuk interalia, darat, laut dan ekosistem air dan ekologi kompleks, itu termasuk keanekaragaman dalam spesies dan ekosistem. Tujuan penulisan skripsi ini adalah untuk memahami jenis – jenis keanekaragaman hayati dan untuk melestarikan keanekaragaman hayati kepada pengunjung. Metode yang digunakan dalam penulisan skripsi ini dengan melakukan studi pustaka dan referensi jurnal, penulis mencari bahan – bahan melalui internet. Pengelola kebun binatang memerlukan pengunjung untuk kelangsungan dan kemajuan pengelolaan kebun binatang, untuk itu promosi dan penyebarluasan informasi menjadi hal yang penting. Di era digital ini informasi dapat mudah dijangkau oleh sarana smartphone yang jumlah penggunanya setiap tahun terus bertambah, dan bisa menjadi captive market untuk pengelola kebun binatang. Kebun binatang belum memanfaatkan media teknologi untuk kebutuhan pengelolaan sarana informasi dan promosi. Penggunaan aplikasi QR code ini memberikan kemudahan bagi pengunjung kebun binatang karena akses informasi dan promosi jauh lebih efektif dan fleksibel bagi pengunjung, karena tidak perlu lagi akses beberapa kali untuk mendapatkan informasi dan promosi. Dengan adanya aplikasi QR code pengelola kebun binatang dapat memanfaatkan dan menggunakan sebagai media informasi dan media promosi kepada pengunjung kebun binatang. Aplikasi QR code yang digunakan untuk sarana penyampaian promosi dan Informasi di kebun binatang adalah Zxing Library. Kata Kunci : QR code, Promosi, Informasi, Binatang, Smartphone Android